Amniotic membrane graft (AMG) for persistent epithelial defects following infective corneal ulcers and keratitis – A systematic review - Thanigasalam Thevi; Adinegara L Abas; Harminder S Dua (Indian Journal of Ophthalmology, 2025)
Management of nonhealing corneal ulcers is challenging as it can lead to complications such as melting, descemetocele, and perforation, which can be prevented by amniotic membrane graft (AMG). The absence of any review (English language) on AMG for corneal ulcers prompted us to conduct this review. We looked for clinical trials (randomized and controlled) on the effect of AMG combined with other treatments, through various search engines utilizing the terms amniotic membrane and corneal ulcer. All patients who received AMG and/or conventional medication were included. Risk of bias tools derived from Cochrane collaboration were used to ascertain the standard and quality of the trials. Visual acuity and epithelial healing time were the main outcome measures studied. Three trials were finally selected for analysis. AMG was noted to be associated with better uncorrected visual acuity and reduction in neovascularization. There was no difference in best corrected visual acuity, epithelial healing time, and corneal opacity. There is evidence that the use of AMG is associated with improved uncorrected visual acuity as well as reduction in neovascularization of the cornea among patients with corneal ulcers, but there was no improvement in epithelial healing time or corneal opacity. Further multicenter randomized controlled trials are needed to elicit the beneficial effects of the intervention and augment the validity of this review.